Shading as a conditioning factor to forest species planting: a study with Apuleia leiocarpa - Carpenedo Aimi, Suelen; Machado Araujo, Maristela; da Silva Tonetto, Thaíse; Almeri Tabaldi, Luciane; Witt Saldanha, Cleber; Gomes Farias, Júlia; Gomez de Oliveira, Gisele (BOSQUE, 2017)
This study aimed at identifying the most appropriate level of shading for initial growth of Apuleia leiocarpa seedlings, through their survival, morphological and physiological/biochemical parameters. The following treatments were evaluated: 0 (full sun), 18, 50 and 70 % of shading. Survival was assessed at 30 and 360 days after planting and morphological parameters such as height (H), stem diameter (SD) and H/SD ratio were measured bimonthly for a year. Physiological parameters as contents of chlorophyll a, chlorophyll b, chlorophyll a/b ratio, carotenoids, lipid peroxidation, acid phosphatase enzyme activity, initial fluorescence, máximum fluorescence, maximum quantum yield of photosystem II and electron transport rate were estimated at 180 and 360 days after planting. At 30 days after planting (d.a.p) there was no mortality of Apuleia leiocarpa seedlings influence of different levels of shading. In the assessments performed at 180 and 360 d.a.p., there was no significant difference among levels of shading for H and SD. However, high mortality rates were observed at 360 d.a.p., especially in full sun. Morphological and physiological parameters of Apuleia leiocarpa plants showed this species requires shading (18 and 50 %) in their early stages of growth.